Haemato-Biochemical Alterations in Cattle Naturally Infected with Lumpy Skin Disease - Raval, Jigar B; Raval, Sunant K; Kanani, Amit N; Sadhu, Dashrath B (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
Lumpy skin disease (LSD) is an emerging viral disease of cattle, causing substantial economic losses due to decreased productivity and increased morbidity. This study investigated haematological and biochemical alterations in LSD-affected cattle (n=150) compared to healthy controls (Group A, n=25). LSD-infected animals were categorised according to the severity of infection based on clinical signs in to Group B: Mild LSD infection (n=42), Group C: Moderate LSD infection (n=84), and Group D: Severe LSD infection (n=24). Infected animals exhibited significant leukopenia, lymphopenia, neutrophilia, macrocytic hypochromic anaemia, and thrombocytopenia in accordance with the severity of the disease. Biochemical analysis showed reduced total protein and albumin with elevated blood urea nitrogen, creatinine, ALT, and AST, particularly in severe cases, and these alterations were also in accordance with the severity of the disease. The values of almost all haemato-biochemical parameters were significantly (p<0.01) altered from those of healthy controls. These findings highlight the utility of blood and serum biochemical profiling as valuable diagnostic and prognostic tools for timely disease detection and effective management in endemic regions.